Effectiveness of the Using DSC Application to Physical and Mental Health Care in Patients with Non-Communicable Diseases - Prakhinkit, Susaree; Njamjuntratip , Kanjana; Pantapitikun , Sutatip (Journal of Nursing, Siam University, 2024)
Objective: To development and determine the effectiveness of Daily Self Care (DSC) application for physical and mental health care in patients with Non-Communicable Diseases (NCDs) to blood pressure, blood sugar, and stress. Method: The research was quasi-experimental research. It was conducted in 2 phases, the first phase was to study the development of DSC and the second phase was to study the effectiveness of DSC application for physical and mental health care in patients with NCDs to blood pressure, blood sugar and stress. The data was analyzed compare the mean scores before and after within group by Pair t-test. Independent t-test was used to compare between groups. Results: The development DSC application to physical and mental health care divided into 2 parts. Part 1 is an application for users consisting of 6 functions, including stress assessment before and after activities, exercise activities: 5 happiness, guidelines for mental health care, knowledge about diabetes, blood pressure diseases and part 2 web application for system administrators receive data for self-care of users .The results of the effectiveness DSC application analysis found that 1) The subjects who used DSC application for physical and mental health care had significant decreased blood pressure significantly (p<0.05) 2) The subjects who used DSC application for physical and mental health care had significant decreased blood sugar significantly (p<0.05) 3) The subjects who used DSC application for physical and mental health care had decreased stress significantly (p<0.05) Conclusion: The DSC application for physical and mental health care could and decreased blood pressure, blood sugar and relief stress.